Combination blockade of KLRG1 and PD-1 promotes immune control of local and disseminated cancers. (1st January 2021) - Tata, Angela; Dodard, Garvin; Fugère, Céline; Leget, Corinne; Ors, Mélody; Rossi, Benjamin; Vivier, Eric; Brossay, Laurent
ABSTRACT: Checkpoint blockade therapy is effective against many cancers; however, new targets need to be identified to treat patients who do not respond to current treatment or demonstrate immune escape. Here, we showed that blocking the inhibitory receptor Killer cell lectin-like receptor G1 (KLRG1) enhances anti-tumor immunity mediated by NK cells and CD8 + T cells. We found that loss of KLRG1 signaling alone significantly decreased melanoma and breast cancer tumor growth in the lungs of mice. In addition, we demonstrated that KLRG1 blockade can synergize with PD-1 checkpoint therapy to increase the therapeutic efficacy compared to either treatment alone. This effect was even observed with tumors that do not respond to PD-1 checkpoint therapy. Double blockade therapy led to significantly decreased tumor size, increased frequency and activation of CD8 + T cells, and increased NK cell frequency and maturation in the tumor microenvironment. These findings demonstrate that KLRG1 is a novel checkpoint inhibitor target that affects NK and T cell anti-tumor immunity, both alone and in conjunction with established immunotherapies.